A ciência como regeneradora da nação : eugenia e autoritarismo no pensamento de Oliveira Vianna, Azevedo Amaral, Renato Kehl e Belisário Penna - Munareto, Geandra Denardi (2017)
The objective of this work is to analyze the association between Eugenics and Authoritarianism in the works of Belisário Penna, Renato Kehl, Oliveira Vianna and Azevedo Amaral, not only related to the diagnoses of national problems, but also in their projects for the future. They saw not only the disorganization of the nation as a problem to be solved, but also the inability of the ruling elites to perceive them, proposing appropriate solutions, as well as the impossibility of an inferiorized, sick and dysgenic population in providing means for the country achieve prosperity. Eugenics and Authoritarianism appear as solutions that would enable the long-awaited path to progress and modernity, but its effectiveness would depend on a joint action between these two proposals, as that alone they would not be able to overcome the three main causes of national backwardness: race, elites, and political-institutional organization.